National Trends in Lumbar Degenerative Spondylolisthesis With Stenosis Treated With Fusion Versus Decompression - Jacob R. Ball; Matthew C. Gallo; Kareem Kebaish; Nicole Hang; Andy Ton; Fergui Hernandez; Marc Abdou; William J. Karakash; Jeffrey C. Wang; Raymond J. Hah; Ram K. Alluri (Neurospine)
Objective The purpose of this study is to describe utilization, demographics, complications, and revisions for patients with degenerative spondylolisthesis (DS) with stenosis undergoing decompression or decompression with fusion in the United States. Methods A national insurance database was used to identify patients who underwent either decompression and fusion or decompression alone for management of DS from 2010–2022. Utilization trends, demographics, and complications for each procedure were compared. Results A total of 162,878 patients were identified, of which 78,043 patients underwent combined single-level lumbar decompression and fusion and 84,835 underwent single-level lumbar decompression alone. Between 2010–2021, lumbar decompression and fusion became the predominant surgical intervention for DS in 2016 and continued to account for more than half of all procedures during the remainder of the study period. Factors such as age, sex, comorbidities, geographic region, and physician specialty training were associated with procedure choice. Decompression with fusion was associated with a lower risk of revision surgery up to 5 years postoperatively and an overall lower incidence of 30-day complications. Conclusion Decompression with fusion has become the most common treatment for lumbar DS over the past decade despite a lack of compelling evidence supporting its use compared to decompression alone. A variety of patient and surgeon-specific factors is associated with procedure choice. After accounting for cofounders, we identified treatment-specific complications that may be valuable when counseling patients.